2019
DOI: 10.3389/fmicb.2019.02325
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effect of 1,8-Cineol on Pathogenic Bacteria Species Present in Chronic Rhinosinusitis

Abstract: Chronic rhinosinusitis (CRS) is marked by an inflamed mucosa of sinuses and is accompanied by a significantly reduced quality of live. Since no guidelines for the treatment of CRS are available, long lasting clinical histories with health care costs adding up to dozens of billion $ annually are caused by CRS. The progression of CRS is often induced by bacterial infections and/or a shift in microbiome as well as biofilm formation. The exact microbiome alterations are still unclear and the impenetrable biofilm r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…In contrast to the strong bactericidal effects against S. aureus, cell Next to Gram-positive bacterial species such as S. aureus, we also investigated potential anti-bacterial properties of our invasomes and particularly, thymol-invasomes on Gram-negative E. coli. Here, cineol-comprising invasomes led to a strong inhibition of E. coli growth, which is in line with our previous observations [13]. In contrast to the strong bactericidal effects against S. aureus, cell growth of Gram-negative E. coli was not affected by thymol-invasomes.…”
Section: Growth-inhibition Zone Assay Shows Strong Bactericidal Activsupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast to the strong bactericidal effects against S. aureus, cell Next to Gram-positive bacterial species such as S. aureus, we also investigated potential anti-bacterial properties of our invasomes and particularly, thymol-invasomes on Gram-negative E. coli. Here, cineol-comprising invasomes led to a strong inhibition of E. coli growth, which is in line with our previous observations [13]. In contrast to the strong bactericidal effects against S. aureus, cell growth of Gram-negative E. coli was not affected by thymol-invasomes.…”
Section: Growth-inhibition Zone Assay Shows Strong Bactericidal Activsupporting
confidence: 92%
“…We found our terpenoids-invasomes to be bactericidal against Gram-positive S. aureus, with increasing efficiency from cineol-and camphor-invasomes (moderate bactericidal activity) to thymol-invasomes showing the strongest bactericidal effects. These findings are in line with the commonly reported bactericidal activity of thymol, camphor and cineol [10,12,13]. Interestingly, Mulyaningsih and colleagues reported that exposure of MRSA even to high concentrations of cineol does not inhibit multi-resistant S. aureus.…”
Section: Growth-inhibition Zone Assay Shows Strong Bactericidal Activsupporting
confidence: 84%
See 2 more Smart Citations
“…Furthermore, both Eucalyptus globulus essential oil and 1,8-cineole prevented biofilm formation by methicillin-resistant Staphylococcus aureus (MRSA) and subsequently the spreading of nosocomial infection. A recent study reports genetic downregulation of biofilm induction in chronic rhinosinusitis by 1,8-cineole with inhibition of relevant microbial pathogens (S. aureus, Escherichia coli, Moraxella catarrhalis) and pro-inflammatory NF-jB target genes at relevant concentrations [70]. This may be of further relevance, since in another study the microbiome profile was assessed by using sequencing of the 16S rRNA gene for the followup of hospitalized patients with acute exacerbated COPD (AECOPD) who did not survive with higher Staphylococcus levels [71].…”
Section: Antimicrobial and Antiviral Effects Of 18-cineole And Essenmentioning
confidence: 99%